(untitled) (Eurasian Journal of Philology Science and Education, 2015)
The article considers the Kazakh literature of the second half of the twentieth century, including the directions of the Kazakh novel’s research development. In the 1950-90s, the novel became the most relevant genre in Kazakh literature. Therefore, the research of the novel genre is the main problem of the Kazakh and world literary criticism. The aim of the article is to reveal the artistic–idealistic search for the relation between man and society, man and nature connection, touching upon the authorial credo concerning the attitude of man to freedom; and to know the author’s principles through literary solutions. At the same time, the author describes the requirements of contemporary literary research, spirit of people through the human inner world on the way to independence during the Soviet time. It is also pointed out that it is necessary to research all human problems in Kazakh novels in relation with current spiritual world of mankind. The main idea of Kazakh novels in the 1950-90s was to depict real reasons of independence and analyze artistic decisions, to define the meaning of the national idea; all of these issues were scientifically substantiated in the article